Media Komunikasi - Mesiono, Rahmiyatul Mawaddah, Novia Elisa Harahap (Ability: Journal of Education and Social Analysis, 2021)
In the implementation of formal education (school education), it is clear that the role of communication is very prominent. The teaching and learning process is mostly due to the communication process, both intra-personal and interpersonal communication. Therefore, it is important for us to become skilled at communicating, and to know the principles of communication in both education and society. This type of research is library research, which is a series of studies relating to the method of collecting library data, or research where the object of research is explored through a variety of library information (books, encyclopedias, scientific journals, newspapers, magazines, and documents). The research result shows that communication is the process of delivering or receiving messages from one person to another, either directly or indirectly, in writing, orally or in nonverbal language. Communication in education is a communication or interaction that occurs in the world of education, in fact it plays a very large role in determining the success of the education concerned